Barreras para acceder a los servicios de rehabilitación de la baja visión: Una revisión de tema (2020)
Objective: to analyze the barriers reported in the literature for access to low vision rehabilitation services.Methods: a narrative review based on scientific literature published in the period 2008 to 2019 and linked in the Pubmed, Scielo, Ebsco and Science Direct databases was conducted.Results: the barriers reported by health care providers were related to the lack of knowledge in low vision and the limited number of professionals engaged in care as well as the invisibilation of care in eye care plans.  The barriers expressed by people are related to lack of information and knowledge about low vision services, difficulties in displacement/transport and fear of stereotypes.Conclusions: barriers to access rehabilitation services are complex, and some can be addressed more easily than others. Improving the training of human resources, and generating channels of communication between professionals and people may reduce those barriers. Stigma associated with visual impairment is an element that appears to be crucial and needs to be addressed.